2021
DOI: 10.11648/j.ajche.20210903.12
|View full text |Cite
|
Sign up to set email alerts
|

CO<sub>2</sub> Valorization Reactions over Cu-Based Catalysts: Characterization and the Nature of Active Sites

Abstract: Active sites are the individual reactors at the molecular scale distributed on the heterogeneous catalyst surface. To a large extent, they determine the catalytic performances and the reaction pathway of a reaction. Therefore, understanding the nature and structure of the actives sites is crucial to improve and develop novel, robust and practical catalysts. The wide application of state-of-the-art characterization techniques these years makes it possible to obtain crucial information about the active sites for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 203 publications
(365 reference statements)
0
6
0
Order By: Relevance
“…Electroreduction of CO 2 is another appealing approach for CO 2 valorization. The principles of operation, striking features, and the challenges of this process have been discussed in the literature [10,12,[60][61][62]. The electrochemical CO 2 reduction is a multielectron and multiproton process involving several transfer pathways that result in different products [63], and this is of immense advantage over the single electron process in terms of electrochemical potential requirements [62].…”
Section: Electrocatalytic Activation Of Comentioning
confidence: 99%
See 2 more Smart Citations
“…Electroreduction of CO 2 is another appealing approach for CO 2 valorization. The principles of operation, striking features, and the challenges of this process have been discussed in the literature [10,12,[60][61][62]. The electrochemical CO 2 reduction is a multielectron and multiproton process involving several transfer pathways that result in different products [63], and this is of immense advantage over the single electron process in terms of electrochemical potential requirements [62].…”
Section: Electrocatalytic Activation Of Comentioning
confidence: 99%
“…Yu et al [96] demonstrated through spin-polarized DFT calculations that adsorption and dissociation of CO 2 was dependent on the Co particle size. They showed that Co 55 nanoclusters had the highest CO 2 dissociation activity in comparison to Cu-based materials have gained much attention in the CO 2 conversion process due to their wide applicability in the different conversion processes and low cost [12,97]. Despite these and other massive studies, the activation of CO 2 on Cu catalysts is still an issue due to the poor understanding of its mechanism.…”
Section: Co 2 Activation On Representative Pure Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a hexagonal crystal structure and is thermally and chemically stable. ZnO is a conducting oxide that has astonishing chemical and electrical properties with applications in electronics, pharmaceutical and petrochemical industries [12][13][14][15][16][17][18]. It is known that wurtzite ZnO crystals show four low-index surfaces: (101 ̅ 0), (112 ̅ 0), (0001), (0001 ̅ ), and the zinc blend ZnO crystal show three low-index surfaces: (100), (110), and (111) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In this process, Cu acts as a catalyst to facilitate the reaction between CO2 and hydrogen (H2) to form methanol (CH3OH). When deposited onto ZnO surfaces, Cu can undergo surface reconstructions that create additional active sites for CO2 and H2 binding [17][18][19]. For example, Cu(001) surfaces have been found to undergo a surface reconstruction known as the Cu(001)-ZnO structure, which creates a network of Cu atoms and ZnO layers that can enhance the activity of the catalyst [18].…”
Section: Introductionmentioning
confidence: 99%